2022
DOI: 10.3389/fphys.2021.749372
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Finite Element Method Model of the Proximal Carpal Row and Experimental Validation

Abstract: The Finite Element Method (FEM) models are valuable tools to create an idea of the behavior of any structure. The complexity of the joints, materials, attachment areas, and boundary conditions is an open issue in biomechanics that needs to be addressed. Scapholunate instability is the leading cause of wrist pain and disability among patients of all ages. It is needed a better understanding of pathomechanics to develop new effective treatments. Previous models have emulated joints like the ankle or the knee but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Anatomically, a type 2 wrist is considered to have a more stable midcarpal joint due to the additional facet with the hamate. 12, 13 Rhee et al concluded that in proven scapholunate dissociation, type 2 lunates were associated with a lower incidence of dorsal intercalated segment instability. 15,16 This study's finding that in a type 2 wrist the carpal bones move in the same direction with excision of the distal pole of the scaphoid, suggests that the bones move as one unit, held together by the more anatomically stable midcarpal joint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anatomically, a type 2 wrist is considered to have a more stable midcarpal joint due to the additional facet with the hamate. 12, 13 Rhee et al concluded that in proven scapholunate dissociation, type 2 lunates were associated with a lower incidence of dorsal intercalated segment instability. 15,16 This study's finding that in a type 2 wrist the carpal bones move in the same direction with excision of the distal pole of the scaphoid, suggests that the bones move as one unit, held together by the more anatomically stable midcarpal joint.…”
Section: Discussionmentioning
confidence: 99%
“…The bones were given the material properties of cortical bone based on the results from several literature sources. [12][13][14] Cancellous bone was omitted in this study, as the literature has shown minimal influence of cancellous bone on force transference and displacement in carpal bones. 13 The scaphoid was then split into proximal and distal halves by cutting the bone at a 40degree angle from its base with the ulna.…”
Section: Simulation Preparationmentioning
confidence: 99%
“…The carpal bones move during flexion and extension of the wrist, which changes the geometry of the carpal canal and consequently affects the movement of tendons and the median nerve; this was not taken into account in this study. However, consideration of the carpal bone interaction is a separate complex task considered in many other studies [11][12][13][14][15]. Adding the effect of carpal bone motion would greatly complicate calculations and increase calculation time to an unacceptable level.…”
Section: Limitationsmentioning
confidence: 99%
“…Scaphoid and lunate bones and scaffold were included in the calculation. Marqués et al 2022 [13] investigated distal carpal row moves. A three-dimensional model of the proximal carpal row was created through DICOM images.…”
Section: Introductionmentioning
confidence: 99%
“…Ligaments constitute an important component of wrist mechanics providing mechanical stability. 39 They have hyperelastic behavior 40 and operate only in tension. 41 A common technique is to model ligaments as springs to simulate their flexibility as semirigid tissue.…”
Section: Cartilage Modelingmentioning
confidence: 99%